2002
DOI: 10.1111/1467-9450.00292
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in major depression

Abstract: Major depression is a mood disorder that is often accompanied by the impairment of cognitive functions. Although suggestive, the large range of existing neuropsychological, neuropsychiatric, and, lately, neuroimaging investigations have not yet given a consistent picture of the psychological and biological disturbances involved in this psychiatric disorder. The present study of the cognitive functions in depression was part of an extensive investigation, including neuropsychological testing, psychiatric examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
111
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(125 citation statements)
references
References 88 publications
10
111
1
3
Order By: Relevance
“…Several studies have reported that depressed patients are impaired on verbal fluency tasks (Landro et al 2001;Moritz et al 2002;Ravnkilde et al 2002), Trail Making Tests (Austin et al 1999;Grant et al 2001;Moritz et al 2002), Wisconsin Card Sorting Test (Ilonen et al 2000;Grant et al 2001;Moritz et al 2002), and on the Tower of London task (Beats et al 1996;Elliott et al 1996). There is, however, some inconsistency, the deficit appearing only in endogenous cases in some studies (Austin et al 1999;Rogers et al 2004), while other authors failed to evidence executive functioning deficits in major depression regardless of the severity (Ravnkilde et al 2002). These discrepancies may reflect a number of methodological issues, including variation in diagnostic criteria, test selection and strategies used to perform this task.…”
Section: Cognitive Deficits In Major Depressionmentioning
confidence: 99%
“…Several studies have reported that depressed patients are impaired on verbal fluency tasks (Landro et al 2001;Moritz et al 2002;Ravnkilde et al 2002), Trail Making Tests (Austin et al 1999;Grant et al 2001;Moritz et al 2002), Wisconsin Card Sorting Test (Ilonen et al 2000;Grant et al 2001;Moritz et al 2002), and on the Tower of London task (Beats et al 1996;Elliott et al 1996). There is, however, some inconsistency, the deficit appearing only in endogenous cases in some studies (Austin et al 1999;Rogers et al 2004), while other authors failed to evidence executive functioning deficits in major depression regardless of the severity (Ravnkilde et al 2002). These discrepancies may reflect a number of methodological issues, including variation in diagnostic criteria, test selection and strategies used to perform this task.…”
Section: Cognitive Deficits In Major Depressionmentioning
confidence: 99%
“…Forty-six normal volunteers, mean age 41 AE 11X6 years (range 21±65 years, 16 males/30 females), participated in the study as part of a larger study dealing with affective disorders (Ravnkilde et al, 2001;Videbech et al, 2001aVidebech et al, , 2001bVidebech et al, , 2001c. The subjects were recruited by newspaper advertisement and had an average of 12X4 AE 2X4 years of education.…”
Section: Subjectsmentioning
confidence: 99%
“…Patients with MDD often present deficits in verbal fluency tests 17,18 , set shifting 10,19,20 , planning 21,22 , and automated response inhibition 10,17,22 . These functions are controlled by the prefrontal cortex and the circuits that some of its different parts establish with the thalamus and the basal ganglia 22,23 .…”
Section: Introductionmentioning
confidence: 99%